Memahami Pendekatan Penelitian - Idhar Idhar; Arif Nur Fadhil; Rika Sa’diyah (Peneliti.net, 2026)
This study aims to comprehensively explain and understand the types and approaches of qualitative, quantitative, and mixed methods research that are often used by researchers. The research method used is a qualitative descriptive method using literature review with the aim of describing, explaining, and analyzing each social phenomenon. The results of the discussion show that the qualitative research approach provides an understanding of social phenomena based on meaning and context, the quantitative research approach emphasizes data measurement, variables, and statistical data analysis to test the validity of hypotheses, while the mixed methods research approach is a combination of both qualitative and quantitative approaches with the aim of producing more complete and valid research.